Comparison between different methods of sonographic cervical length assessment during pregnancy - Abd Naby Awad, El Sayed El Badawy Mohamed; Dayem, Tamer Mamdouh Abdel; El-Agwany, Ahmed Mohammed Samy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm birth is the presence of uterine contraction of sufficient frequency and intensity to effect progressive effacement and dilatation of cervix prior to term gestation (between 20 and 37 weeks). The objective of this study was to compare between the different methods of assessment of cervical length (Trans abdominal, trans vaginal, and transperineal) during pregnancy as a possible screening of preterm birth. Methods: Prospective cohort study was performed on 200 cases who attended at Elshat by hospital. At gestational age from 20 to 26 weeks, there was no significant difference regarding demographic data as (maternal age, parity). The route of examination was started according to urinary bladder fullness at admission. Accordingly, the patient was not instructed to void if she had full bladder, rather we started by transabdominal route. If she had empty bladder at the time she presented we started by transperineal then transvaginal route. The four measurements were compared to each other and the difference between them calculated. The selected sample size was found to be 200 pregnant women. Results: Transvaginal route gave the longest cervical measurements followed by transperineal route then abdominal route (full bladder) and finally tans abdominal route (semi-full bladder). Our results indicate that there is a significant positive correlation among the four methods of measuring cervical length in that gestational age. Conclusions: Tran-abdominal assessment could be used initially for cervical length screening, considering the maternal and fetal condition. Then, if the need arises, transvaginal sonography could be used. This step by step approach may be more convenient and useful to both patients and physicians for cervical length screening.